2018
DOI: 10.1111/pce.13493
|View full text |Cite
|
Sign up to set email alerts
|

Role of cyclic and pseudo‐cyclic electron transport in response to dynamic light changes in Physcomitrella patens

Abstract: Photosynthetic organisms support cell metabolism by harvesting sunlight and driving the electron transport chain at the level of thylakoid membranes. Excitation energy and electron flow in the photosynthetic apparatus is continuously modulated in response to dynamic environmental conditions. Alternative electron flow around photosystem I plays a seminal role in this regulation contributing to photoprotection by mitigating overreduction of the electron carriers. Different pathways of alternative electron flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 63 publications
(99 reference statements)
1
40
0
Order By: Relevance
“…In C. reinhardtii (Jokel et al, 2018), PGRL1 plays an important role in the response to FL, although it takes some time to activate. Moreover, in Physcomitrella patens, PGRL1 is mostly active under continuous light (Storti et al, 2019). By contrast, in P. tricornutum, a chlorophyll c-containing organism, we found that PGRL1 plays an important role in responding to fluctuating light.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In C. reinhardtii (Jokel et al, 2018), PGRL1 plays an important role in the response to FL, although it takes some time to activate. Moreover, in Physcomitrella patens, PGRL1 is mostly active under continuous light (Storti et al, 2019). By contrast, in P. tricornutum, a chlorophyll c-containing organism, we found that PGRL1 plays an important role in responding to fluctuating light.…”
Section: Discussionmentioning
confidence: 56%
“…Studies have shown that an absence of PGRL1 in A. thaliana, which are sensitive to AA, causes a decrease of CET. Recently, studies have indicated that PGRL1 acts synergistically with FLV under fluctuating light conditions (Storti et al, 2019). In C. reinhardtii (Jokel et al, 2018), PGRL1 plays an important role in the response to FL, although it takes some time to activate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant material and growth P. patens (Gransden ecotype) wild-type (WT) and flva, pgrl1 and ndhm knockout (KO) lines (Kukuczka et al, 2014;Gerotto et al, 2016;Storti et al, 2019Storti et al, , 2020 were maintained in the protonemal stage by vegetative propagation on PpNH 4 medium (Ashton et al, 1979) and grown under controlled conditions: 24°C, 16 h : 8 h, light : dark photoperiod with 50 µmol photons m À2 s À1 (control light, CL) unless otherwise specified. Physiological and biochemical experiments were performed on 10-d-old plants grown in PpNO 3 medium (Ashton et al, 1979).…”
Section: Methodsmentioning
confidence: 99%
“…For triple mutant isolation, the pgrl1 construct was used to remove pgrl1 from the flva-ndhm background. Similarly, the ndhm KO construct (Storti et al, 2020) was used to remove the gene from the flva-pgrl1 KO background (Storti et al, 2019), obtaining triple flva-pgrl1-ndhm KO mutant plants in both cases (Fig. S2).…”
Section: Moss Transformation and Mutant Selectionmentioning
confidence: 99%